Negative Effects Of Protamine On Myocardium In Paediatrics Patients Undergoing Cardiac Surgery Using A Cardiopulmonary Bypass Machine - Suprayitno Suprayitno; Dhama Shinta S; William M; Muhammad Eros Z S; Ameru U; Atya Sabrina M (International Journal of Social Service and Research, 2023)
The administration of protamine, a heparin reversal agent, is an integral part of cardiovascular bypass protocols, particularly in the post-bypass phase. In paediatric cases, protamine is administered in a titration dose. The use of protamine is associated with various adverse events, including myocardial impairment. Proper dosage adjustment is crucial during protamine administration, as excessive doses may result in the depression of myocardial function. Experimental studies examining protamine usage have revealed myocyte impairments, such as reduced myocyte contractility, dysfunction in signaling pathways, and alterations in cardiac receptors. Despite these findings, research on the impact of pediatric protamine on the myocardium remains limited and necessitates further investigation.